Factores ambientales y su influencia en las alergias respiratorias en niños de 5 a 7 años en la Unidad Educativa Manuel Cordova Galarza de Ventanas octubre 2018 - abril 2019 - Flores Mera, Gabriela Karina (2019)
The development of the work focused on environmental factors and their influence on respiratory allergies in children aged 5 to 7 years, for which purpose was established to determine the influence of environmental factors on respiratory allergies in children aged 5 to 7 years of the Educative Unit Manuel Córdóva Galarza de Ventanas October 2018 - April 2019, therefore, the most vulnerable group of students aged 5, 6 and 7 years with respiratory allergies was identified, through surveys of parents of families, who will provide information about the environment and the child's health; We identified the most frequent causes that affect the appearance of respiratory allergies in children of 5, 6 and 7 years old and the level of knowledge parents have about respiratory allergies and how to prevent them. Within the methodology of the research, a quantitative and qualitative approach was required, in order to know the antecedents, and the detection of acute respiratory allergies in children 5 to 7 years old, in order to determine the causes that they present, the types of research applied were the explanatory one. , descriptive, correlational and field. The technique used was the survey which obtained results that corroborated the assumptions is that the factors identified in the research are the cause of respiratory allergies in children, which is why it was established as a proposal Preventive educational talks on respiratory allergies to the parents of children from 5 to 7 years of age in the Manuel Córdova Galarza de Ventanas Educational Unit, in this way it will be possible to take correct measures to improve the quality of life of the children.